The Storfjorden, Svalbard, earthquake sequence 2008-2020: Transtensional tectonics in an arctic intraplate region - Ottemöller, Lars; Kim, Won-Young; Waldhauser, Felix; Tjåland, Norunn; Dallmann, Winfried (Seismological Research Letters, 2021)
An earthquake sequence in the Storfjorden offshore area southwest of Spitsbergen in the Svalbard archipelago initiated with a 21 February 2008 magnitude M w 6.1 event. This area had previously not produced any significant earthquakes, but between 2008 and 2020, a total of ∼ 2800 earthquakes were detected, with ∼ 16 of them being of moderate size ( M L ≥ 4.0 ). Applying double‐difference relocation to improve relative locations reveals that the activity is linked to several subparallel faults striking southwest–northeast that extend across the entire crust. The southwest–northeast trend is also found as a possible fault plane from regional moment tensor inversion. The solutions range from oblique normal in the center of the cluster to pure strike slip farther away and are consistent with the compressional σ 1 axis roughly in the east–west direction and plunging 57°, and the extensional σ 3 axis subhorizontal trending north–south. The mainshock fault is steeply dipping to the southeast, but several other faults appear to be near vertical. The existence of oblique, right‐lateral strike‐slip motion on southwest–northeast‐trending faults with a normal component and pure normal faulting events in between suggests transtensional tectonics that in and around Storfjorden result in activation of a complex fault system.